Pengembangan Bahan Ajar Berbentuk Modul Geometri Analitik Ruang bagi Mahasiswa Program Studi Pendidikan Matematika FKIP UNBARI - Harman Harman; Sri Dewi (Universitas Batanghari Jambi, 2022)
Spatial Analytical Geometry is one of the compulsory subjects in the S1 Education curriculum of the Mathematics Education Study Program. Learning Geometry Analytical Space is expected to be able to create a paradigm for students to use mathematics in everyday life. The purpose of this study was to develop teaching materials in the form of Spatial Analytical Geometry modules and to determine the quality of teaching materials in the form of modules developed based on the feasibility aspect. This research is a development research using the Research & Development method of the Borg and Gall model which has been modified by Sugiyono, namely the stages: (1) Potential and Problems, (2) Collecting Data, (3) Product Design, (4) Design Validation, (5) Design Revision, (6) Product Trial, (7) Product revision. The results of this study indicate that at the product validation stage carried out by material experts on the aspect of content feasibility, an average value of 3.3 was obtained with the criteria of